2011
DOI: 10.1097/fjc.0b013e318210fc7e
|View full text |Cite
|
Sign up to set email alerts
|

Concomitant Angiotensin AT1 Receptor Antagonism and Neprilysin Inhibition Produces Omapatrilat-like Antihypertensive Effects Without Promoting Tracheal Plasma Extravasation in the Rat

Abstract: Dual inhibition of angiotensin-converting enzyme (ACE) and neprilysin (NEP) by drugs such as omapatrilat produces superior antihypertensive efficacy but cause high incidence of angioedema. We examined whether dual inhibition of angiotensin AT1 receptor (ARB) and NEP (ARB-NEPI, valsartan-candoxatril) provides similar efficacy to omapatrilat without the risk of angioedema. Activity of test compounds at the targets was assayed using fluorescence-based enzyme assays (ACE, NEP, aminopeptidase P) or competition bind… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
42
1
3

Year Published

2013
2013
2020
2020

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(47 citation statements)
references
References 44 publications
1
42
1
3
Order By: Relevance
“…17,18 LCZ696, which consists of the neprilysin inhibitor sacubitril (AHU377) and the ARB valsartan, was designed to minimize the risk of serious angioedema. 19,20 In small trials involving patients who had hypertension or heart failure with a preserved ejection fraction, LCZ696 had hemodynamic and neurohormonal effects that were greater than those of an ARB alone. 21,22 We examined whether the long-term effects of LCZ696 on morbidity and mortality were superior to those of ACE inhibition with enalapril in patients with chronic heart failure and a reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…17,18 LCZ696, which consists of the neprilysin inhibitor sacubitril (AHU377) and the ARB valsartan, was designed to minimize the risk of serious angioedema. 19,20 In small trials involving patients who had hypertension or heart failure with a preserved ejection fraction, LCZ696 had hemodynamic and neurohormonal effects that were greater than those of an ARB alone. 21,22 We examined whether the long-term effects of LCZ696 on morbidity and mortality were superior to those of ACE inhibition with enalapril in patients with chronic heart failure and a reduced ejection fraction.…”
Section: Discussionmentioning
confidence: 99%
“…15,16 Therefore, the preferred approach to parallel modulation of these neurohormonal systems is the combined use of a neprilysin inhibitor with an angiotensin receptor blocker. 17 The PARADIGM-HF (Prospective comparison of ARNI with ACEI to Determine Impact on Global Mortality and morbidity in Heart Failure) trial compared the long-term effects of LCZ696-a complex of the neprilysin inhibitor sacubitril and the angiotensin receptor blocker valsartan-with enalapril in patients with heart failure with mild-to-moderate symptoms. 18 The trial demonstrated the superiority of LCZ696 over enalapril on both death from any cause, and on death from cardiovascular causes.…”
Section: Editorial See P 11 Clinical Perspective On P 61mentioning
confidence: 99%
“…13,14 In a preclinical model, ARNi (using valsartan-candoxatril) provided similar antihypertensive efficacy as omapatrilat without inducing tracheal plasma extravasation (a surrogate of angioedema). 15 LCZ696 has been the first ARNi to be evaluated in patients with hypertension and HF. [16][17][18] LCZ696 combines a moiety of the ARB valsartan and the NEPi precursor, AHU377.…”
Section: Clinical Perspective On P 78mentioning
confidence: 99%